PENGEMBANGAN VIDEO ANIMASI BERBASIS KARAKTER CINTA TANAH AIR UNTUK ANAK USIA DINI - Miranda, Dian (Universitas Tanjungpura, 2019)
AbstrakThe aim of this study is to develop animated characters based on love of homeland for early childhood. The research method used in this study is R & D research. The development model in this study refers to the 4D research and development model (four-D). According to Thiagarajan (1974) the 4D research and development model consists of 4 main stages, namely define, design, develop, and disseminate. The data analysis technique used in this study is a mixed analysis technique that is a combination of qualitative analysis and quantitative analysis. The results of video validation carried out by 4 validators were an average of 2.8 with a maximum score of 3, included in the very feasible category used as learning media to develop the character of love for the homeland in early childhood.Kata Kunci: animated video, the character of love for the homelandÂ